Disentangling the Evidence of Milankovitch Forcing From Tree-Ring and Sedimentary Records - Helama, Samuli; Herva, Hannu; Arppe, Laura; Gunnarson, Björn; Frank, Thomas; Holopainen, Jari; Nöjd, Pekka; Mäkinen, Harri; Mielikäinen, Kari; Sutinen, Raimo; Timonen, Mauri; Uusitalo, Joonas; et al. (Frontiers in Earth Science, 2022)
Tree-ring records constitute excellent high-resolution data and provide valuable information for climate science and paleoclimatology. Tree-ring reconstructions of past temperature variations agree to show evidence for annual-to-centennial anomalies in past climate and place the industrial-era warming in the context of the late Holocene climate patterns and regimes. Despite their wide use in paleoclimate research, however, tree rings have also been deemed unsuitable as low-frequency indicators of past climate. The arising debate concerns whether the millennia-long tree-ring records show signals of orbital forcing due to the Milankovitch cycles. Here, we produce a summer-temperature reconstruction from tree-ring chronology running through mid- and late-Holocene times (since 5486 BCE) comprising minimum blue channel light intensity (BI). The BI reconstruction correlates with existing and new tree-ring chronologies built from maximum latewood density (MXD) and, unlike the MXD data, shows temperature trends on Milankovitch scales comparable to various types of sedimentary proxy across the circumpolar Arctic. Our results demonstrate an unrevealed potential of novel, unconventional tree-ring variables to contribute to geoscience and climate research by their capability to provide paleoclimate estimates from inter-annual scales up to those relevant to orbital forcing.